Join IDNLearn.com today and start getting the answers you've been searching for. Join our interactive Q&A community and get reliable, detailed answers from experienced professionals across a variety of topics.
Sagot :
Answer:
5
Step-by-step explanation:
Remark
Start with the meaning of g[f(x)]. This when you write g(x), where ever you see and x in g(x), put in an f(x)
g(f(x))
g(x)= x + 1 Substitute f(x) for x
g(f(x)) = f(x) + 1 Substitute x^2 for f(x)
g(f(x)) = x^2 + 1
g(f(-2)) = (-2)^2 + 1 Substitute -2 for x
g(f(-2)) = (4) + 1
g(f(-2)) = 5
We are happy to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. IDNLearn.com has the solutions you’re looking for. Thanks for visiting, and see you next time for more reliable information.